Sistematik Review: Kriteria dan Peran Pengawas Menelan Obat Pasien Tuberculosis di Indonesia - Fina Ratih Wira Putri (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2019)
Indonesia falls into the category of countries with the highest TB case burden. This number will continue to increase if the number of TB patient care is not implemented properly. Non- compliance with treatment is a separate problem in the success of TB elimination. The role of Supervisor for Drug Swallowing/Pengawas Menelan Obat (PMO) is one of the factors that support the success of TB treatment. The purpose of this study was to determine the criteria and role of supervisors to swallow drugs in tuberculosis patients in Indonesia. Two article search engines were used, namely GARUDA (Garba Rujukan Digital) and Neliti. There are 14 types of research identified, with details of 10 quantitative studies and 4 qualitative studies. The expected criteria of the Supervisor for Drug Swallowing/Pengawas Menelan Obat (PMO) are over 17 years old, female, not working, minimum high school education having kinship relations, living at home, and if the supervisor swallows drugs is a health worker then has better knowledge about tuberculosis treatment and empowerment of TB patients to form a self group. The role of Supervisor for Drug Swallowing/Pengawas Menelan Obat (PMO) in Indonesia includes ensuring patients swallow drugs every day, become educators, accompany control patients to health care centers, remind patients to check recurrent phlegm, provide moral support to patients, take patients to health care centers if drug side effects occur, improve preventive behavior and increase body weight.